Design, fabrication, and decontamination of low-cost microfluidics for nucleic acid amplification - Vi T. Nguyen; Clifford Anderson; Karen S. Anderson; Jennifer Blain Christen (Sensors and Actuators Reports)
Liquid assays, such as polymerase chain reaction (PCR) and loop-mediated isothermal amplification (LAMP), are difficult to implement in point-of-care microfluidic devices because bubbles often form. We present a reaction chamber design called same-depth inlet outlet (SDIO), which was found to reduce the instances of bubble formation by an average of 92.2 % across different flow rates when compared to traditional designs. We designed the fabrication process using xurography, laser cutting, and lamination techniques, which enable rapid and low-cost prototyping. The fabrication methods were evaluated for nuclease contamination, and best practices to reduce nucleases during and after chip assembly are detailed. Our technique, using a combination of ethanol rinses and ultraviolet-C light radiation, was found to reduce RNases up to tenfold. Different materials were tested for microfluidic compatibility with LAMP assay reagents by making chips that realistically emulate final surface areas and volumes. A variation in performance was found among different adhesives, where the best fluorescence ratio between positive and negative reactions was 4.63. Our microfluidic design was validated by amplifying a spiked RT-LAMP assay with SARS-CoV-2 primers in the reaction chambers. The overall findings aim to facilitate early-stage development and prototyping of microfluidic devices with consistent and reliable results.